2012
DOI: 10.4000/discours.8623
|View full text |Cite
|
Sign up to set email alerts
|

Genre Realized in Theme: The Case of News Reports and Commentaries

Abstract: The purpose of this paper is to analyze how the clausal thematic features observed in two newspaper genres —news reports and commentaries— can be interpreted as textual signals of their different generic characterization. This is done through the qualitative and quantitative analysis of a sample consisting of thirty-three English texts, divided into two groups of seventeen news reports and sixteen commentaries, respectively. The analysis focused on the following thematic features: (1) the experiential elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…The results of this study lend support to the findings of prior studies; (e.g., Pokasumit, 2009;Lavid et al, 2012;McCabe &Heilman, 2007 andFahimeh &Nabifar, 2013). These studies also utilized linguistic and functional grammar analysis in newspapers with varying purposes in language for communication.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study lend support to the findings of prior studies; (e.g., Pokasumit, 2009;Lavid et al, 2012;McCabe &Heilman, 2007 andFahimeh &Nabifar, 2013). These studies also utilized linguistic and functional grammar analysis in newspapers with varying purposes in language for communication.…”
Section: Discussionsupporting
confidence: 90%
“…Topic and theme are incorporated with each other to introduce a super corpus of the message. Lavid et al (2012) studied "Genre Realized in Theme: The Case of News Reports and Commentaries" of two newspapers using thematic structure to analyze news' texts and found that certain thematic features are needed for each newspaper. "An extremely important aspect of functional grammar is the way information is structured in communication" (Bloor & Bloor, 2004 p. 64).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their incidence ranged between 32 and 47% of clauses, which was consistent with the frequency identified in other hard news corpora (Shindo 2001;McCabe and Heilman 2007). Alongside visual methods of informational organisation such as the headline/lead nucleus (White 1997) and paragraphing, textual Themes organise the logico-semantic relations in order to "scaffold the text's argumentative structure" (Lavid, Arús and Moratón 2012). This could explain the higher rate of textual Theme in the French articles compared to the American ones, where the former's debate format necessitates a clearer organisation of complex ideas since there are multiple arguments interacting within the text.…”
Section: Journal Of World Languages 121supporting
confidence: 71%
“…In this section, we focus on a micro-thematic analysis of the articles to explain how Theme-Rheme structures at the clause level affirm the "correlation between genre and thematic content" (Lavid, Arús and Moratón, 2012). Further studies may apply a macrothematic analysis, based on Danes' (1974) theory of thematic progression, to reveal the thematic hierarchies and interrelations within a text, although previous studies only weakly support the hypothesis that thematic progression (as opposed to the thematic structure at clause level on which we focus our analysis) correlates with genre (Francis 1989(Francis , 1990; as cited in Fries 1995).…”
Section: Theme and Information Flowmentioning
confidence: 99%
“…Showing similarities to news reports, the two genres are also different: while news reports are objective and use neutral language in presenting various opinions and sources (White 1998), commentaries often contribute to the formulation of a preferred viewpoint . The two genres are also different with respect to thematic roles as Lavid et al (2012) note, more specifically the thematic head that Lavid et al define as "the first nuclear experiential constituent within the main clause" (2012: 9) expressed by the subject or the complement in the preverbal position of the main clause and carrying experiential roles such as actor, carrier, recipient, attributor, sayer, etc. Based on the findings, both genres have a high frequency of Actor as an experiential role, yet there is a higher percentage of the thematic role of Sayer in news reports, as compared to commentaries, where the thematic role of Carrier prevails .…”
Section: Journalistic Commentariesmentioning
confidence: 99%